ЕВОЛЮЦІЯ СВІТЛА У ЖИВОПИСІ ОЛЕКСАНДРА МУРАШКА - Мосендз Оксана Олегівна (International Journal of Innovative Technologies in Social Science, 2019)
The aim of the work is to identify evolution in search of ways to transmit light in the work of Alexander Murashko. Considering the artist’s work from the first studies to the last masterpieces, one can observe the difficult creative path of the master. Soft, diffused light in the first works, still bearing the imprint of icon-painted canons of lighting. Realism in the transmission of lighting in paintings created under the guidance of I. Repin. The play of light and reflexes, the radiance of night lights, the transmission of light-air space - these are the discoveries of the Impressionists, who replenished the artist’s palette. Decorativeism, sculpting forms with the help of light - these helped Murashko to nourish Modern. Having absorbed all these components into his work, synthesizing them, enriching them with Ukrainian folk color, A. Murashko created his own unique style, piercing the canvas with the radiance of sunlight.